Primary synovial chondromatosis of the ankle: A case report with radiologic and imaging findings - Morteza Gholipour; Mohsen Salimi; Alireza Motamedi; Fatemeh Abbasi; Bahar Behnam; Seyyedeh Reyhaneh Sadr (Radiology Case Reports)
Synovial chondromatosis (SC) is a rare, benign joint disorder characterized by cartilaginous nodule formation within the synovial membrane. While SC typically affects larger joints such as the knee and hip, ankle involvement is exceptionally uncommon, with only a few cases documented in medical literature. We present a case of a 38-year-old male who experienced a rare presentation of recurrent ankle sprains and a palpable mass, ultimately diagnosed with SC in the ankle. Initial arthroscopic treatment proved insufficient due to the extensive loose bodies within the joint, necessitating a follow-up open arthrotomy to ensure complete excision. Postoperative recovery was favorable, with no recurrence observed at follow-up. This case underscores the importance of considering SC in patients with unexplained joint instability and mechanical symptoms, even in atypical joints like the ankle. Surgical intervention, particularly open arthrotomy, remains crucial for achieving effective management in advanced cases and preventing recurrence. This case report contributes to the limited literature on ankle SC and highlights the need for awareness of this rare presentation to facilitate early diagnosis and intervention.